Application of Models to Eutrophication in Lakes - Serap PULATSÜ (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2022)
One of the phenomena that causes ecological concerns is lake eutrophication. Lakes are under the threat of water quality degradation and ecological imbalance due to increased anthropogenic activity, particularly in developing countries. In this context, limnologists and environmental scientists have been using numerical modeling in their studies of aquatic ecosystems over the last few decades. Ecological models use ecosystem-process interactions to simulate future management scenarios and evaluate the system's response to eutrophication. Utilizing ecological models has made it simpler than ever to estimate and manage lake eutrophication. However, due to lake-specific issues, the models are becoming increasingly detailed. In this review ; a) The model types used in eutrophication-focused modelling studies were summarized b) Model utilizations based on different eutrophication elements and events were highlighted via several recent national and international studies.